Effect of Organic Matter on Boron Adsorption by Some Soils of Punjab - Arora, Harsh; Bhardwaj, S.S.; Sharma, B.D. (Asian Journal of Chemistry, 2010)
Boron, one of the essential micronutrient elements, has a marked effect on plants, from the standpoint of both plant nutrition and toxicity. Organic matter is one of the main sources of boron in soils. Therefore, the present investigation was undertaken to study the effect of organic matter on boron adsorption by twelve soils of Punjab. Results revealed that there was a decrease in the adsorption of boron with the removal of organic matter content in majority of the soils except in some soils of semi-arid and arid regions. In most of these soils there was a negligible change in adsorption with the removal of organic matter.